Increased Electrical Conductivity of Carbon Nanotube Fibers by Thermal and Voltage Annealing - Varun Gangoli (C: Journal of Carbon Research, 2021)
We report the effect of annealing, both electrical and by applied voltage, on the electrical conductivity of fibers spun from carbon nanotubes (CNTs). Commercial CNT fibers were used as part of a larger goal to better understand the factors that go into making a better electrical conductor from CNT fibers. A study of thermal annealing in a vacuum up to 800 °C was performed on smaller fiber sections along with a separate analysis of voltage annealing up to 7 VDC; both exhibited a sweet spot in the process as determined by a combination of a two-point probe measurement with a nanoprobe, resonant Raman spectroscopy, and X-ray photoelectron spectroscopy (XPS). Scaled-up tests were then performed in order to translate these results into bulk samples inside a tube furnace, with similar results that indicate the potential for an optimized method of achieving a better conductor sample made from CNT fibers. The results also help to determine the surface effects that need to be overcome in order to achieve this.